Chất lượng mối quan hệ giữa ngân hàng và khách hàng đối với hành vi mua chéo của khách hàng: Trường hợp Bancassurance Việt Nam - Phan Thu , Hiền; Phan Chung , Thủy; Lê Văn , Lâm (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
In recent years, cross-buying (or selling) has contributed greatly to the revenue of Vietnamese banks, helping the banking system to overcome the most difficult period due to the COVID-19 pandemic. One of the most popular cross-buying (or selling) activities today is buying insurance distributed through banks (Bancassurance). The paper examines the influence of relationship quality (including satisfaction and trust), perceived value and image on customers' cross-buying behavior on Bancassurance in Vietnam. Using an in-depth interview technique with banking experts, the research results show that “relationship quality” plays the most important role in customers' cross-buying behavior for Bancassurance. When considering the aspects of relationship quality, “trust” is considered to have a stronger influence than “satisfaction”. Besides, “image” is also considered in the cross-buying decisions of customers. In contrast, customers' perceived value of insurance products has almost no impact on their cross-buying behavior.
Keywords: Bancassurance; Relationship quality; Cross-buying behavior; Vietnam